Strong-interaction effects in stop pair production at e+e- colliders - Drees, M. [UNESP]; Éboli, O. J P [UNESP] (Springer Nature, 1999)
We discuss perturbative and non-perturbative strong-interaction effects in the pair production of stop squarks (t̃1) at e+e- colliders. Events with an additional hard gluon allow to detect or exclude t̃1t̃*1 production even in scenarios with very small mass splitting between ti and an invisible lightest supersymmetric particle (LSP). Such events can also help to establish that t̃1 transforms as a triplet under SU(3)C. We also carefully study non-perturbative t̃1 fragmentation, which is currently not well understood: not only is the t̃1 fragmentation function not known very well, but also there are ambiguities in the algorithm employed to model fragmentation. We present numerical results both for CERN LEP-183 and for a proposed future e+e- collider operating at center-of-mass energy s1/2 = 500 GeV.